PENGARUH ISLAM DALAM PERWUJUDAN WAYANG KULIT PURWA - Drs. Sunarto, M.Hum (Ars: Jurnal Seni Rupa dan Desain, 2006)
In Islam expanding in Jaw, known to have prohibition order about depiction of mortal, what hitherto still trusted by society, enjomment depiction of the mortal its wide o f impact especially at fine arts growth in Indonesia. One of the effect ofenjoiment depiction of mortal in Islam is materialization ofpurwashadow play. Prohibiton order depiction o f that mortal bring advantage in shadow play growth in Indonesia, that is creation form puppets whish stilistik with depiction o f purwa puppets by ideoplastik, a way of materialization o f mortal able to be accepted in Islam teaching.Keyword: mortal, purwa shadow play, prohibition order.